Global Health Neurology: HIV/AIDS - Patel, Payal B.; Spudich, Serena S. (Seminars in Neurology, 2018)
With the advent of combination antiretroviral therapies, the mortality rate from HIV has declined, while the prevalence of long-term HIV-related neurologic complications continues to rise. Thirty-six million individuals are living with HIV around the world, many of whom reside in resource-limited settings. The majority of studies have focused on individuals residing in the developed world, while the impact of HIV disproportionately affects people living in developing countries. This review focuses on recent domestic and international studies regarding neurologic complications related to HIV, including opportunistic infections, peripheral neuropathy, cerebrovascular disease, and HIV-associated neurocognitive disorders, in light of the growing population affected by these conditions.
Keywords: human immunodeficiency virus; global health; HIV-associated neurocognitive disorders; peripheral neuropathy; cerebrovascular disease